Implications and Challenges of GIS in Geological Exploration - Dr. Krishna Gopal (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Geographical Information Systems (GIS) have become indispensable tools in geological exploration, transforming how geologists analyze and visualize spatial data. By integrating geological, geophysical, and geochemical information, GIS enables more efficient resource mapping, environmental monitoring, and hazard assessment. Its application in mineral exploration allows for the precise identification of potential resource deposits and the mapping of geological structures, significantly improving the accuracy and speed of exploration efforts. In addition, GIS plays a crucial role in assessing geohazards, such as landslides, earthquakes, and volcanic activity, helping geologists mitigate risks and make informed decisions. The use of GIS in geological exploration is not without challenges. Issues such as data accuracy, integration difficulties, and the high costs associated with GIS technology can pose significant barriers. There is a need for specialized training in GIS software and techniques to fully capitalize on its potential. Despite these challenges, GIS continues to offer tremendous advantages, such as cost and time efficiency, real-time data analysis, and enhanced decision-making capabilities. Looking ahead, advancements in GIS technology, including the use of machine learning and real-time geological sensor data, promise to further enhance its applications. This article explores the implications and challenges of GIS in geological exploration, providing insights into its transformative role while addressing the ongoing challenges that need to be overcome to maximize its benefits. Through a deeper understanding of these factors, geologists can better leverage GIS to drive more efficient and effective exploration practices.